Glyoxalase 1 and its substrate methylglyoxal are novel regulators of seizure susceptibility. (14th February 2013) - Distler, Margaret G.; Gorfinkle, Naomi; Papale, Ligia A.; Wuenschell, Gerald E.; Termini, John; Escayg, Andrew; Winawer, Melodie R.; Palmer, Abraham A.
Summary Purpose Epilepsy is a complex disease characterized by a predisposition toward seizures. There are numerous barriers to the successful treatment of epilepsy. For instance, current antiepileptic drugs have adverse side effects and variable efficacies. Furthermore, the pathophysiologic basis of epilepsy remains largely elusive. Therefore, investigating novel genes and biologic processes underlying epilepsy may provide valuable insight and enable the development of new therapeutic agents. We previously identified methylglyoxal (MG) as an endogenous γ‐aminobutyric acid (GABAA) receptor agonist. Here, we investigated the role of MG and its catabolic enzyme, glyoxalase 1 (GLO1), in seizures. Methods We pretreated mice with MG before seizure induction with picrotoxin or pilocarpine and then assessed seizures behaviorally or by electroencephalography (EEG). We then investigated the role of GLO1 in seizures by treating mice with a pharmacologic inhibitor of GLO1 before seizure induction with pilocarpine and measured subsequent seizure phenotypes. Next, we explored the genetic relationship between Glo1 expression and seizures. We analyzed seizure phenotypes among C57BL/6J × DBA/2J (BXD) recombinant inbred (RI) mice with differential Glo1 expression. Lastly, we investigated a causal role for Glo1 in seizures by administering pilocarpine to transgenic (Tg) mice that overexpress Glo1. Key Findings Pretreatment with MG attenuated pharmacologically‐induced seizures at both the behavioral and EEG levels. GLO1 inhibition, which increases MG concentration in vivo, also attenuated seizures. Among BXD RI mice, high Glo1 expression was correlated with increased seizure susceptibility. Tg mice overexpressing Glo1 displayed reduced MG concentration in the brain and increased seizure severity. Significance These data identify MG as an endogenous regulator of seizures. Similarly, inhibition of GLO1 attenuates seizures, suggesting that this may be a novel therapeutic approach for epilepsy. Furthermore, this system may represent an endogenous negative feedback loop whereby high metabolic activity increases inhibitory tone via local accumulation of MG. Finally, Glo1 may contribute to the genetic architecture of epilepsy, as Glo1 expression regulates both MG concentration and seizure severity.